2022
DOI: 10.1111/jeb.14030
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric density‐dependent competition does not contribute to the maintenance of sex in a mixed population of sexual and asexualPotamopyrgus antipodarum

Abstract: The maintenance of sexual reproduction remains an important question in evolutionary biology (Neiman et al., 2018). The question arises in part because sexual females produce male offspring, which do not bear young, whereas asexual females produce only daughters. This gives asexuals an intrinsic twofold advantage over their sexual counterparts, which is called the 'cost of males ' (Lively & Lloyd, 1990;Maynard Smith, 1978). The cost of males has been demonstrated in several systems, including Amazon Mollies (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
3
1
0
Order By: Relevance
“…By contrast, there was a trend toward native lineages producing the most embryos in low density. This result is similar to that of Dinges and Lively ( 2022 ), where mesocosm experiments showed that reproduction of native P . antipodarum lineages was negatively affected by high population density.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…By contrast, there was a trend toward native lineages producing the most embryos in low density. This result is similar to that of Dinges and Lively ( 2022 ), where mesocosm experiments showed that reproduction of native P . antipodarum lineages was negatively affected by high population density.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, there was a trend toward native lineages producing the most embryos in low density. This result is similar to that of Dinges and Lively (2022), where mesocosm experiments showed that reproduction of native P. antipodarum lineages was negatively affected by high population density. In our experiment, nativelineage snails produced relatively few embryos in intermediate and high density, which echoes trends reported for native-range P. antipodarum in Cope and Winterbourn (2004).…”
Section: Embryo Productionsupporting
confidence: 87%
See 2 more Smart Citations